User Consultation Behaviour in Internet Dictionaries: An Eye-Tracking Study - Simonsen, Henrik Køhler (HERMES - Journal of Language and Communication in Business, 2011)
The purpose of this paper is to explore and discuss user consultation behaviour on the basis of eye-tracking data and interview data. To date the focus has been almost exclusively on the use of log ﬁles in Internet lexicography – an approach which is questioned in this article. The paper is based on empirical data from an exploratory eye-tracking study of the user consultation behaviour of six participants and on interview data from a follow-up post-study interview of the participants. The paper elucidates and discusses the consultation behaviour in Internet lexicography and shows not only at what the participants looked, but also how they accessed lexicographic data. The paper presents a suitable method for using eye-tracking studies in Internet lexicography and advocates an increased use of this method to produce empirical data upon which additional theoretical considerations on the information and data access process can be developed. Finally, the implications for further research in user consultation behaviour are brieﬂy explored.